Learning web platform design and implementation - Wang, Chuanqi (2019)
As we know with the rapid development of information technology nowadays, people are using the internet as a platform to access information. Web pages and websites have become an important foundation in Internet networking. Web page design is especially important to attract users, such as web pages with excellent visual effects, rich information, and convenient using. The course of computer network basic principle knowledge has always been the most difficult course for readers who want to learn computer network knowledge. The purse of this final year project is to design and develop a website about introducing networking application layer knowledge for the beginners. At the same time, the website provides a broad communication platform for learners to communicate with each other and encourage each other to promote learning results. A CMS is a free open source system that connects a front-end web page to a back-end management system. A website can be built by using CMS themes, functional plugins, and components. According to the original intention of the website design and development, it is a good choice to build a website using the very famous WordPress in CMS. The project was successfully implemented the basic functionalities for the learners. Finally, the testing results show that the website can basically meet the learners’ needs.